2006
DOI: 10.1259/bjr/58438178
|View full text |Cite
|
Sign up to set email alerts
|

Resources and costs associated with incidental extracolonic findings from CT colonogaphy: a study in a symptomatic population

Abstract: CT colonography (CTC) is increasingly used to detect colonic polyps and cancers, but its impact in practice is also influenced by frequent detection of extracolonic lesions. We have previously documented the frequency and nature of such lesions. The current study was performed to assess the clinical resources and costs associated with the investigation and treatment of extracolonic lesions. We reviewed the reports of 225 consecutive CTC examinations carried out on patients with symptoms of bowel cancer. 116 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 14 publications
6
64
1
Order By: Relevance
“…Similar studies have been undertaken for different specialities such as CT colonography or cardiac CT [6][7][8].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar studies have been undertaken for different specialities such as CT colonography or cardiac CT [6][7][8].…”
Section: Discussionmentioning
confidence: 94%
“…This lies in part with the scans themselves, but also in the incidental extra-urinary findings from these scans. Other studies have evaluated the costs of incidental findings in CT colonography or coronary CT [6][7][8] and have demonstrated a significant economic burden in the follow-up and investigation of these patients. The vast majority of incidental findings do not need definitive treatment, so the costs cannot be completely balanced by the early identification of treatable disease.…”
mentioning
confidence: 99%
“…72 Increased testing inevitably produces more positive results, leading to knock-on investigations, adding further to the number of tests ordered. 71,73 The motivation for ordering a test can be conceptualised under two non-exclusive categories: technical factors related to the diagnosis and management of disease and social factors. The latter include reassurance for patient and/or doctor, patient expectation and maintaining the doctor-patient relationship.…”
Section: Substudiesmentioning
confidence: 99%
“…26 A literature review of 18 studies reported that of a cumulative 3,280 patient who underwent CTC, 1,763 incidental findings were detected, of which only 3.7% were cancers or aortic abdominal aneurysms. 27 In addition to the emotional burden on patients, it has also been estimated that incidental ECFs add $297 (US) per patient to the overall cost of CTC. 27 Therefore, although ECFs are a potential benefit of CTC, the financial cost, human resource burden, and patient impact cannot be overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…27 In addition to the emotional burden on patients, it has also been estimated that incidental ECFs add $297 (US) per patient to the overall cost of CTC. 27 Therefore, although ECFs are a potential benefit of CTC, the financial cost, human resource burden, and patient impact cannot be overlooked.…”
Section: Resultsmentioning
confidence: 99%